The communicative approach to studying Ukrainian as a foreign language in the main stage (Philological Studies: Scientific Bulletin of Kryvyi Rih State Pedagogical University, 2015)
The paper deals with the analysis of scientists’ views concerning the term «approach». The communicative approach, its intention and advantages in the main stage of studying Ukrainian as a foreign language are accentuated.
Keywords: approach; communicative approach; Ukrainian as a foreign languag; the main stage of studying Ukrainian